The causes of differences opinions among jurists / Aida Khairani Zaidi … [et al.] - Zaidi, Aida Khairani; Yusri, Atikah Nabilah; Mohd Fauzi, Nur Athirah; Mohd Jalani, Nursolehah; Hashim, Rohani (2023)
Differences of opinion or differences among scholar to determine a law are not only unavoidable but will continue to occur in the realm of religion. In fact, differences of opinion have existed since the days of the Companions and continued until the birth of the main schools of jurisprudence such as Hanafi, Maliki, Syafi'e and Hanbali as well as several other groups of mujtahid imams. Although the scholars in each sect have a method of issuing laws that are partly different in determining the law, they are still guided by the same source, which is alQuran and and as - Sunnah. In giving an opinion about a religious law, it must be done by a jurist. Jurist or fuqaha' in terms of language means who is expert in Islamic Law. They also must expert about al- Quran and sunnah because they will provide the law to all the muslims. While, difference of opinion or ikhtilaf in terms of language means there is no agreement and agreement on something or in other words a difference of opinion on something. While in terms of terms, a difference of opinion means the non-existence of a consensus by every scholar on an issue. The word difference of opinion here refers to the difference of opinion of mujtahid scholars in a problem that hovers between two parties who differ in opinion due to the hidden part of the evidence or failure to find those arguments. It will cause a difference in the law issued by the mujtahid scholars in fiqh matters, either in the opposite form, such as one side thinks it should be in an issue, while the other side thinks it is haram or something else.